Morphological peculiarities of peritoneal adhesions in patient with acute peritoneal adhesions obstruction and impaired liver function - Ilyina-Stognienko V.Ju. (Морфологія, 2012)
The features of morphological structure of adhesions in acute adhesive intestinal obstruction in patients with impaired liver function were investigated. It was found that in patients with impaired liver function observed greater adhesions in the abdominal adhesions polymorphism, the presence of fibrin and inflammatory infiltration in the remote period after previous laparotomy. In patients without liver dysfunction adhesions formed by dense connective tissue, moderately vascularized covered with mesothelium, fibrin and inflammatory infiltration absent. These data suggest a predisposition to progression of adhesions in the remote period after laparotomy in patients with impaired liver function.